A conventional PCR technique to detect Septoria tritici in wheat seeds - Consolo, Verónica Fabiana (2009)
A PCR assay was developed for detection of wheat seed naturally contaminated with Septoria tritici. S. tritici specific primers were derived from strict alignment of ITS and a-tubulin sequences of the pathogen. The specificity of four sets of synthesised oligonucleotide pairs (A, B, C and D) were tested using isolates from S. tritici, other selected fungi and wheat seeds. A single DNA fragment was amplified from S. tritici isolates with all primer pairs, whereas no product was generated from otherDNAsources. S. tritici was also detected in wheat seed lots collected from plants with variable pycnidial coverage on the upper two leaves. PCR detection of as little as 0.5 pg of S. tritici genomic DNAwas possible. This is the first report on the detection of S. tritici DNA in naturally infested wheat seeds. This PCR based assay is simple, rapid, specific, sensitive and suitable for routine detection of the wheat pathogen in infested wheat seeds.